Association between non-variceal spontaneous portosystemic shunt and outcomes after TIPS in cirrhosis. Issue 12 (December 2018) - He, Chuangye; Lv, Yong; Wang, Zhengyu; Guo, Wengang; Tie, Jun; Li, Kai; Niu, Jing; Zuo, Luo; Yu, Tianlei; Yuan, Xulong; Chen, Hui; Wang, Qiuhe; et al.
Abstract: Background: Whether pre-existing nonvariceal spontaneous portosystemic shunts (SPSSs) in cirrhotic patients affect outcomes after transjugular intrahepatic portosystemic shunt (TIPS) and whether they need to be closed remains unclear. Aim: To assess the effects of the presence or embolization of SPSSs on outcomes after TIPS for cirrhosis. Methods: From January 2004 to December 2014, 903 consecutive cirrhotic patients who underwent TIPS in a tertiary-care center were included, of which 715 patients had no SPSS (N-SPSS group), 144 patients had an SPSS without embolization (SPSS group), and 44 had an SPSS with embolization (SPSS + E group). Results: During a median follow-up period of 27.7 months, 368 (41%) patients experienced overt hepatic encephalopathy (OHE), 256 (28%) experienced clinical relapse, 164 (18%) developed shunt dysfunction, and 379 (42%) died. The SPSS group had a higher risk of OHE compared with the N-SPSS and SPSS + E groups (adjusted HR [95%CI]: N-SPSS vs SPSS vs SPSS + E: 1 vs 1.36 [1.06–1.75] vs 0.77 [0.46–1.29]; p = 0.027). In stratification analysis, a higher risk of OHE was only observed in patients with a large SPSS (SPSS diameter ≥6 mm) but not a small SPSS. Additionally, SPSS embolization was associated with a lower risk of OHE among patients with a large SPSS (adjust HR = 0.51; 95% CI: 0.29–0.91; p = 0.034). The risks of clinical relapse (p = 0.584), shunt dysfunction (p = 0.267), and mortality (p = 0.4743) did not significantly differ among groups. Conclusions: Among cirrhotic patients undergoing TIPS, a pre-existing large SPSS was associated with a higher risk of OHE, which could be decreased by SPSS embolization. There was no clear association between the presence/embolization of an SPSS and post-TIPS clinical relapse, shunt dysfunction or mortality.